2019
DOI: 10.1002/oby.22374
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Reward‐Related Eating: The RED‐X5

Abstract: Objective: The prevalence of obesity has created a plethora of questionnaires characterizing psychological aspects of eating behavior, such as reward-related eating (RRE). The Reward-based Eating Drive questionnaires (RED-9, RED-13) broadly and deeply assess the RRE construct. However, large-sample research designs require shorter questionnaires that capture RRE quickly and precisely. This study sought to develop a brief, reliable, and valid version of the RED questionnaire. Methods: All-subset correlation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…This would considerably reduce participant burden. The ADOPT initiative (Sutin et al ., ) has highlighted several short and psychometrically sound questionnaires of uncontrolled eating, which include the RED‐13/RED‐X5 (Mason et al ., ; Vainik et al ., ).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…This would considerably reduce participant burden. The ADOPT initiative (Sutin et al ., ) has highlighted several short and psychometrically sound questionnaires of uncontrolled eating, which include the RED‐13/RED‐X5 (Mason et al ., ; Vainik et al ., ).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 97%
“…constructed the Reward‐related Eating Drive (RED‐13) questionnaire that covers variance spanning from mild to very severe forms of uncontrolled eating (Mason et al ., ). This questionnaire has been recently been shortened (Vainik et al ., ) and highlighted as a core measure in the ADOPT initiative (Accumulating Data to Optimally Predict Obesity Treatment; Sutin et al ., ).…”
Section: Uncontrolled Eating As a Continuummentioning
confidence: 99%
“…The original RED‐9 was developed using questions from validated scales and involved soliciting topic expert opinions to ensure high content validity (Epel et al, 2014). The RED‐9 showed good internal consistency (ω = .87–.91 across 5 studies) and test–retest reliability ( r = .77 over a 6‐month period; Vainik, Eun Han, et al, 2019), and predicted the change in BMI from baseline ( β = .05) at an 8 year follow‐up (Epel et al, 2014). Across several studies, the RED‐13 showed better coverage of the lower end of the constructs continuum compared to the RED‐9, providing superior sensitivity to subtle changes in reward‐based eating drives, which is beneficial for understanding uncontrolled eating in non‐clinical samples (Mason et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The RED‐13 is an updated, further validated version that better covers the broader continuum of uncontrolled eating (Mason et al, 2017). The RED‐13 used item‐response theory to select questions that, across numerous studies, precisely probed three phenotypes: perceived loss of control over eating, lack of satiety, and preoccupation with thoughts about food (Mason et al, 2017; Vainik, Eun Han, et al, 2019). Therefore, the RED‐13 is well‐positioned to clarify the heritability of uncontrolled eating and how its genetic factors overlap with BMI, as it provides improved estimation of loss of control over eating and lack of satiety, and uniquely measures preoccupation with thoughts about food, which is an important uncontrolled eating phenotype that has not been examined in prior twin studies.…”
Section: Introductionmentioning
confidence: 99%
“…Reward based eating was assessed using the Rapid Assessment of Reward-Related Eating Drive (RED-X5). 41 The RED-X5 consists of five questions to assess current behaviour regarding overconsumption and preoccupation with food (eg, I don’t get full easily), answered on a 5-point Likert Scale (0/Strongly disagree to 4/Strongly agree). Responses are summed to give a total score (0–20), where a higher score indicates stronger reward-based eating.…”
Section: Methods and Analysismentioning
confidence: 99%